Community Economic Empowerment through Creative Economic Program in a Business Cooperative in Setu District, Tangerang Selatan - Syahrullah Syahrullah; Muhtadi Muhtadi (Universitas Islam Negeri Walisongo Semarang, 2021)
This study aims to determine the process and results of empowering the community's economy through the creative economy program at the Cipta Boga Multipurpose Cooperative. This research was conducted using a qualitative research approach with a descriptive type of research. The data collection techniques used, namely: observation, interviews, and documentation studies. Observations were carried out thematically about the process of community empowerment in the creative economy. Five informants were interviewed, consisting of the management of the cooperative and three program beneficiaries. The selection of informants is based on the fact that they know and are involved in empowerment activities. The documentation study was conducted by collecting data on the process and empowerment program in the creative economy sector at the cooperative. This study indicates that community economic empowerment through a paper bag training program can improve the welfare of the Kranggan village community. The Seba Usaha Cipta Boga Cooperative carries out the stages of community empowerment, starting from planning, implementation, institutionalization, and monitoring evaluation. The influence of the training program results can be seen from the behavior and economic life of the community. People get additional income, increase knowledge in entrepreneurship and get activities for entrepreneurship.